A comparative analysis of conviction outcomes of American domestic terrorists - Murray, Kimberly (International journal of comparative and applied criminal justice, 2018)
This research uses quantitative analyses to determine whether or not conviction outcomes differ across three major American domestic terrorism groups: ecoterrorists, left-wing extremists, and right-wing extremists. Findings suggest that ecoterrorists receive lighter treatment within the criminal justice system while controlling for important variables, such as gender, age, and count severity. Findings highlight differences between “home-grown” terrorist groups, departing from a large segment of terrorism research focused on domestic versus international comparisons or terrorist versus civilian comparisons. Results elicit new research questions to understand why domestic terrorists receive differential treatment within the criminal justice system, despite controlling for key variables.